Pyro-phototronic effect enhanced ZnO nanowire-based tri-layer heterojunction for visible light sensing and communication. (December 2020) - Peng, Wenbo; Pan, Zijian; Li, Fangpei; Cai, Yahui; He, Yongning
Abstract: Photodetector's performances can be effectively enhanced by utilizing the polarization charges generated at the local interface through the light-self-induced pyro-phototronic effect. In order to efficiently take advantage of the polarization charges of both polarities, here a tri-layer heterojunction consisting of one pyroelectric semiconductor ZnO nanowire and other two conventional semiconductors is prepared and its response characteristics to 648 nm laser illuminations are studied. The photocurrents at all the illuminant powers are significantly improved by the pyro-phototronic effect. At illuminant power of 0.04 mW, the responsivity is improved from 0.823 to 22.054 mA/W. Moreover, the effect of chopper frequency has been studied, showing that with the increase of chopper frequency, the photocurrent as well as responsivity first increases and then gradually saturates. Specifically, the responsivity at a chopper frequency of 400 Hz is nearly four times as large as that at 10 Hz, indicating possible applications in ultrafast pulsed light detection. In addition, the intermediate ZnO nanowire layer has been modulated to investigate its influence on the pyro-phototronic effect in this kind of tri-layer heterojunction devices. The results conclude that short ZnO nanowire layer is preferred as the intermediate layer for better pyro-phototronic effect improved device performances. At last, a visible light communication system using the tri-layer heterojunction device is demonstrated, successfully transmitting and decrypting the sent signal. This work provides deep understandings of the physical working mechanisms of the pyro-phototronic effect in tri-layer heterojunction devices, and also exhibits the huge potential of the tri-layer heterojunction devices in high performance photodetection and light communication. Graphical abstract: Image 1 Highlights: ZnO nanowire based tri-layer heterojunction is demonstrated for enhancement of pyro-phototronic effect. The intermediate ZnO layer's preference is short ZnO nanowires for optimizing the pyro-phototronic effect. A visible light communication system is proposed for transmission and decryption of encrypted light input signal.